MAGNETIZING THE INTEREST AND RETENTION OF LECTURER IN PRIVATE HIGHER EDUCATION - Nasir Nasir (International Journal of Educational Management and Innovation, 2020)
Education This study aimed to explore the strategy to maintain lecturers, particularly in private higher education. It is important because the growth of private universities makes qualified lecturers contested. Responding to that crisis, leaders imposed to construct a strategy to keep them. The required data were collected by interviewing selected respondents determined by the key informant. The instrument used in gathering data was a semi-structured interview. The data then analyzed with the inductive model by Miles, Huberman, & Saldana. The result of the study reveals that: higher education should respond to what is prompting lecturers to move. They must take responsibility for every lecturer resigning and to intervene immediately to find out the reasons that make the lecturer to resign. In terms of the strategy to counter the lecturer’s switch out, the researcher constructed a strategy to magnetize them to remain through concerning more seriously on some aspects, for instance: payment, leadership style, career development, conducive-work life, adequate well-resourced libraries, recognition, and workload. All these efforts addressed to motivate them in working then decide to remain in the institution. Lastly, the researcher also recommends to others to test the conclusion by applying a quantitative approach